The Landscape of Exosome-Derived Non-Coding RNA in Leukemia - Tang, Bing-Jie; Sun, Bao; Chen, Lei; Xiao, Jie; Huang, Shu-Ting; Xu, Ping (Frontiers in Pharmacology, 2022)
Leukemia is a group of life-threatening hematological malignancies which is currently incurable and often accompanied by drug resistance or disease relapse. Understanding the pathogenesis of leukemia and finding specific therapeutic targets and biomarkers is of great importance to improve the clinical efficacy of leukemia. Exosome-derived ncRNAs have been demonstrated as critical components of intercellular communication and function as key facilitators in the leukemia biological process. This review outlines the current investigations of exosomal ncRNAs (including miRNA, circRNA, and lncRNA) as important mediators of leukemia and potential therapeutic targets and biomarkers for leukemia treatment. Moreover, we generally analyze the prospects and challenges for exosomal ncRNAs from the aspects of research and clinical application.